2011
DOI: 10.1002/chem.201003716
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Photoswitching Studies of Difurylperfluorocyclopentenes with Extended π‐Systems

Abstract: In an attempt to design molecular optoelectronic switches functioning in molecular junctions between two metal tips, we synthesized a set of photochromic compounds by extending the π-system of 1,2-bis-(2-methyl-5-formylfuran-3-yl)perfluorocyclopentene through suitable coupling reactions involving the formyl functions, thereby also introducing terminal groups with a binding capacity to gold. Avoiding the presence of gold-binding sulphur atoms in the photoreactive centre, as they are present in the frequently us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
44
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 23 publications
4
44
0
Order By: Relevance
“…Taking into account that the determined cyclization time of СF5-TSC is close to all CF5-based DAEs studied by pump-probe spectroscopy [10,12,16] and the relaxation profile has a similar shape [9,11,13], we conclude that the exchange of thiophene against furan apparently has no impact on the ring-closing dynamics of the resulting DAE. Hence, for an application of СF5-based DAE in a combination with gold electrodes, the use of furan-based DAE will be a technical benefit, since oxygen atoms are chemically inert towards gold when compared with sulfur [25].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Taking into account that the determined cyclization time of СF5-TSC is close to all CF5-based DAEs studied by pump-probe spectroscopy [10,12,16] and the relaxation profile has a similar shape [9,11,13], we conclude that the exchange of thiophene against furan apparently has no impact on the ring-closing dynamics of the resulting DAE. Hence, for an application of СF5-based DAE in a combination with gold electrodes, the use of furan-based DAE will be a technical benefit, since oxygen atoms are chemically inert towards gold when compared with sulfur [25].…”
Section: Resultsmentioning
confidence: 99%
“…Both CF and OF are thermally stable, reversibly switchable and have appropriate optical properties (photoconversion quantum yields: cyclization -0.28, cycloreversion -4.910 -3 ) [25], This makes molecules attractive candidates for further applications in the molecularscaled flexible devices with optically modulated properties [4]. However, to use them in a construction of devices with a rapid optical response the dynamics of ring-closing and opening reactions have to be studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[24-25, 27, 31] In one previous study we focused on the synthesis of new sulphur-free photochromic molecules based on the bisfuryl-perfluorocyclopentene core connected to different anchoring groups via -extended wires. [33] The influence of the anchoring group on the electrical conductance through a single-molecule junction and the alignment of the MOs to the Fermi energy level of gold electrodes were systematically studied in a gold-break junction setup. [34][35] From this data it was concluded that for rather short molecules the nature of the anchoring group and side chain (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest in this context is the use of an organic photochromic dye that can be attached to a solid support such as polymer, nanoparticles, or bulk surfaces; providing materials where surface properties such as hydrophobicity, charge, conductivity, colour, molecular recognition, and material size can be easily controlled. Such photoswitchable materials have been proposed for many applications; for example in data storage, [5] nanoelectronics, [6,7] switchable polymers, [8,9] nano-machines, [10,11] gas storage, [12] drugs, [13,14] and sensor devices [15][16][17].…”
mentioning
confidence: 99%